A combined microbial and biogeochemical dataset from high-latitude ecosystems with respect to methane cycle - Barret, Maialet; Gandois, Laure; Thalasso, Frederic; Martinez Cruz, Karla; Sepulveda Jauregui, Armando; Lavergne, Celine; Teisserenc, Roman; Aguilar, Polette; Gerardo Nieto, Oscar; Etchebehere, Claudia; Martins Dellagnezze, Bruna; Bovio Winkler, Patricia; et al. (My University, 2022)
High latitudes are experiencing intense ecosystem changes with climate warming. The underlying methane (CH4) cycling dynamics remain unresolved, despite its crucial climatic feedback. Atmospheric CH4 emissions are heterogeneous, resulting from local geochemical drivers, global climatic factors, and microbial production/consumption balance. Holistic studies are mandatory to capture CH4 cycling complexity. Here, we report a large set of integrated microbial and biogeochemical data from 387 samples, using a concerted sampling strategy and experimental protocols. The study followed international standards to ensure inter-comparisons of data amongst three high-latitude regions: Alaska, Siberia, and Patagonia. The dataset encompasses different representative environmental features (e.g. lake, wetland, tundra, forest soil) of these high-latitude sites and their respective heterogeneity (e.g. characteristic microtopographic patterns). The data included physicochemical parameters, greenhouse gas concentrations and emissions, organic matter characterization, trace elements and nutrients, isotopes, microbial quantification and composition. This dataset addresses the need for a robust physicochemical framework to conduct and contextualize future research on the interactions between climate change, biogeochemical cycles and microbial communities at high-latitudes.
Keywords: Biogeochemical Cycle; Atmospheric methane